Arthrobacter cavernae sp. nov., a novel actinobacterium isolated from sediment of karst cave. Issue 6 (28th June 2022) - Fang, Zheng; Zhao, Xiaoyong; Wu, Qingshan; Li, Shixia; Liu, Qiuping; Tan, Leitao; Weng, Qingbei
Abstract : A novel, Gram-stain-positive, aerobic, non-endospore-forming, non-motile and rod-shaped bacterium designated PO-11 T was isolated from sediment of karst cave collected in Libo county, Guizhou Province, PR China. The isolate grew optimally on R2A agar at 25 °C, pH 8.0 and with 0.5 % (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences showed that PO-11 T belonged to the genus Arthrobacter and was most closely related to Arthrobacter methylotrophus TGA T (98.3 % sequence similarity), Arthrobacter alkaliphilus LC6 T (97.7 %) and Arthrobacter ramosus CCM1646 T (97.1 %). Genome sequencing revealed a genome size of 4 073 119 bp and the genomic DNA G+C content was 66.16 mol%. Its DNA–DNA relatedness values with A. methylotrophus TGA T, A. alkaliphilus LC6 T and A. ramosus CCM1646 T were 23.0, 22.9 and 23.2 %, respectively. The main fatty acids were anteiso-C15 : 0, anteiso-C17 : 0 and iso-C16 : 0 . The major respiratory quinone was MK-9(H2 ). The polar lipids comprised diphosphatidylglycerol, phosphatidylglycerol, glycolipid, phosphatidylethanolamine, phosphatidylinositol and unidentified lipids. Thus, based on phylogenetic and phenotypic and chemotaxonomic data, strain PO-11 T represents a novel species of the genus Arthrobacter, for which the name Arthrobacter cavernae sp. nov. is proposed. The type strain is strain PO-11 T (=CCTCC AB 2021070 T =LMG 32459 T ).